The Evolution of English Morphemes: Sociocultural Perspectives and Future Trajectories - Ellisa Indriyani Putri Handayani; Agus Hari Wibowo (Universitas Cokroaminoto Palopo, 2024)
This research observes at how English morphology changes over time, focused on the changes that happen because of new technologies and social upheavals. This study looks at some important issues related to how cultural changes can affect certain morphological patterns and what might happen in the future with the origins of English words. In this project, a qualitative study method is used to look into language data from academic discourse, digital media, and patterns of communication around the world. The results make clear three important events: the rise of neologisms caused by new technologies; the spread of digital communication morphemes; and the effect of global English on morphological structures. As part of this discussion, these facts are looked at, and it is shown that globalization and digitization encourage morphological innovation, which finally leads to the fast adoption of new morphemes. Another thing it looks at is how these changes affect and show the users' linguistic and cultural traits. The paper comes to the conclusion that English grammatical rules are changing because of how language and social interactions work together. It stresses the need for more research into how important this is for teaching languages and making policy, as well as how computer linguistics can be used to track changes in language in real time.